Β‐Amyloid pathology alters neural network activation during retrieval of contextual fear memories in a mouse model of Alzheimer's disease. (16th March 2014) - Lelos, Mariah J.; Good, Mark A.
Abstract Although episodic memory deficits are the most conspicuous cognitive change in patients with Alzheimer's disease (AD), patients also display alterations in emotional expression, including anxiety and impaired conditioned fear behaviours. The neural circuitry underlying emotional learning is known to involve the amygdala and hippocampus, although the precise impact of amyloid pathology on the interaction between these brain regions remains unclear. Recent evidence suggests that Tg2576 mice, which express a human amyloid precursor protein (APP) mutation associated with early‐onset AD, demonstrate normal acquisition of conditioned freezing to auditory and contextual stimuli paired with footshock. However, examination of the expression of c‐Fos revealed altered neural network activity in transgenic mice. In the present study we examined the effects of the APP mutation on the expression of c‐Fos following the retrieval of emotional memories. To this end, stimulus‐induced cellular activity was measured by analysing expression of the immediate‐early gene c‐Fos after the retrieval of auditory or contextual fear memories. To characterize regional interdependencies of c‐Fos expression, structural equation modelling was used to compare patterns of neural network activity. Consistent with previous findings, Tg2576 mice displayed reduced freezing elicited by the auditory stimulus but not by the conditioning context. Interestingly, the analysis of c‐Fos expression revealed that the APPswe mutation disrupted dentate gyrus and amygdala function, as well as altering the influence of these regions on the neural network dynamics activated during context memory retrieval. These results provide novel insight into the influence of excess amyloid production on neural network activity during memory retrieval.